DESAIN PEMBELAJARAN PPKn KREATIF DAN INTERAKTIF UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA SMP 35 MEDAN - Tawarika M. Pandiangan; Yuli Indriani Lubis; Ida Nurjana Tamba; Ertika S. Pasaribu; Pebryna R. Siburian; Rian Todo Simanjuntak; Liber Siagian; Fazli Rachman (CV. ADIBA AISHA AMIRA, 2023)
The lack of interest in learning Pancasila education and student citizenship is a challenge for the Pancasila education teacher and citizenship address the matter. Furthermore, even poor debriefing and limited teacher preparedness will not be able to accomplish the purposes of a new paradigm as an educational program amplified on his vision of shaping personal quality or making the younger generation into intelligent, characterless, and dependable citizens. Addressing the nature of Pancasila education and citizenship is linked to this study in order to know the success of Pancasila education and citizenship. The article is produced by a qualitative process of study. Data obtained comes from primary data sources with data gathering techniques comes from observation activities and uses secondary data sources. The teachers' design of learning can be adjusted so that the realization of interactive and creative learning can appeal to the passion and achievement of Pancasila education and student citizenship increases.